Decrease Risk Behavior HIV Infected on Construction Laborers with Behavior Change Communication (BCC) Approach - Purwaningsih Purwaningsih; Nasronudin Nasronudin; Nuzul Qur’aniati; Ferry Effendi (Jurnal Ners, 2014)
Introduction: Percentage of HIV-AIDS cases based on the types of work in East Java in 2011 shows that construction workers occupied ranks the top five ranked groups with 249 people (31%) after a group of commercial sex workers (CSWs) group. The purpose of this study was to determine the effectiveness of BCC approach to the reduction of contracting HIV risk behavior in the construction laborers. Method: This study used operational research design. In this study measures the effectiveness of behavior change of construction workers on the prevention of HIV transmission by comparing the behavior of the construction workers before and after the intervention. The subjects of this study were 150 people risk group of construction workers who work and are spread throughout the city of Surabaya. This research was carried out into three phases, namely, phase preintervention research, intervention research, and post-intervention phase of the study. Implemented in the first year and second year praintervensi stage implemented intervention and post-intervention phases.Result: The results of this study showed that 72% of construction workers is productive (18–35 years) and visit his family more than once a month (38%). There is 20% of construction workers had sex with commercial sex workers and no one was using drugs. By 50% of construction workers never get information about HIV/AIDS and as many as 48% never use the services of HIV/AIDS.Discussion: External motivation construction workers associated with the utilization of behavioral HIV/AIDS services with sufficient correlation. Strong external motivation is influenced by risk behaviors of HIV/AIDS were conducted and the desire to get help. Weak external motivation is influenced by a lack of exposure to information related to HIV/AIDS services. The results of the FGD stakeholders have the perception is the same if a construction worker is a high risk group of contracting HIV. Most of the construction workers not have enough knowledge for the prevention of HIV transmission because they do not have access to HIV care and behavior are at risk of contracting HIV by construction workers.